ANALISIS DAN PERANCANGAN PROXY SERVER DENGAN MENGGUNAKAN SQUID PADA KANTOR PUSAT FAKULTAS TEKNIK UNIVERSITAS GADJAH MADA - , MUHAMMAD RADHITIA F.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
With the development of Internet, more and more services are provided to the user. Users of the internet has grown rapidly along with the popularity of the web. This led to increasing demand for internet services. To meet the growing demands, the network is needed to accommodate requests from users. Faculty of Engineering Headquarters (KPFT) UGM provides internet services for students with UGM-Hotspot wireless network. The existing UGM-Hotspot provides internet services to users without any restrictions so that the network becomes less efficient and can be misused. These problems can be overcome by the application of network management, such as proxy server and the Squid. In this study, the methods used in network management is the proxy server and the Squid. These method is suitable to be implemented on KPFT UGM network because there are some proxy servers that are connected to the network and can be combined with the proxy server that will be implementated on KPFT UGM. The use of Squid as a proxy server software is allow the proxy server to communicate with each other. In this study, the implementation of proxy server and the Squid, which allows the limitation of the download speed of the user, web filtering through the Access Control List (ACL) to restrict Web sites that can be accessed and the implementation of the Squid local cache that is connected to the other proxy servers in Faculty of Engineering network to accelerate the opening of frequently accessed web sites. The result is the implementation was successful. Restrictions on download speeds of 3MBps to 256KBps considered optimal in terms of network management for the smooth use of the Internet by all users. Local cache Squid is made to communicate with the other proxy server as a sibling and exchange data from the internet. Web filtering managed to limit the website that can be accessed by the user. Hope that this study can be implemented by the IT staff of KPFT UGM to improve the quality of the existing network.